Exploring the link between BMI and physical fitness in Sichuan’s ethnic minority primary school students: insights from quantile regression analysis - Jingtao Wu; Yanhong Shao; Jun Hu; Xinjuan Zhao (BMC Pediatrics)
Abstract Background Although the nexus between Body Mass Index (BMI) and the physical fitness of the younger demographic has been well-documented, a comprehensive examination of this relationship among children from ethnic minority communities remains unexplored. This study aims to delineate the association between BMI and physical fitness among primary school students in Sichuan’s ethnic minority regions, offering insights to inform health policy tailored to these communities. Methods Utilizing a randomized cluster sampling approach, the study was conducted across ethnic minority regions in Sichuan Province from September to October 2023, encompassing a cohort of 10,800 students from Grade 3 to Grade 6. A spectrum of physical metrics was assessed, including BMI, lung capacity, 50-m sprint, sit-and-reach, rope jumping, abdominal crunches, and shuttle run. Quantile regression analysis was applied, pinpointing 10 BMI quantiles to scrutinize the influence of physical fitness indicators across varying BMI thresholds. Results The results of the study are as follows: (1) A nonlinear dynamic was identified between BMI and physical fitness indicators, with lung capacity demonstrating robust positive correlation with BMI within the intermediate range (45 th to 55 th percentiles) (β = 0.42, p < 0.001), diminishing at the extremes; (2) The 50-m sprint and standing long jump exhibited divergent correlations with BMI, with the sprint showing negative correlation at lower BMI quantiles (5 th to 25 th) and positive at higher quantiles (75 th to 95 th). Conversely, the standing long jump correlated positively within the 10 th to 30 th percentiles and negatively above the 80 th percentile; (3) Pronounced ethnic disparities were noted, particularly with Tibetan students excelling in lung capacity at elevated BMI quantiles (> 80%), showcasing a β difference of 0.15 to 0.23, p < 0.05. Conclusion (1) The correlation between Body Mass Index (BMI) and physical fitness among primary school students from ethnic minorities in Sichuan is not only nonlinear but also exhibits substantial ethnic diversity; (2) An intermediate BMI range—spanning from the 35 th to the 65 th percentiles—correlates most favorably with a broad spectrum of physical fitness indicators.